Dampak Kerusakan Ekosistem Mangrove terhadap Keanekaragaman dan Populasi Perikanan di Teluk Youtefa Kota Jayapura Provinsi Papua - John Dominggus Kalor; Kalvin Paiki (Fakultas Biologi | Universitas Jenderal Soedirman, 2021)
The mangrove ecosystem on the coast of Youtefa Bay is very beneficial for the survival of the Indigenous people in Enggros, Tobati and Nafri villages, as well as residents of Jayapura City and its surroundings. The purpose of this study was to calculate the diversity and population of fisheries in a polluted mangrove ecosystem. The research was conducted in the waters of mangrove ecosystem in Youtefa Bay, Jayapura City, Papua. Fish data were collected at 10 locations, using gill nets with a mesh size of 1.5 inches with a length of 150 meters and 2 inches with a length of 150 meters. Physical and chemical parameters of the waters were also measured in each location. Data analysis used the Shannon-Wiener diversity index, dominance index, fish abundance, and fish species composition. This study only found 12 species and 10 fish families, with an abundance of 188 individuals/ hectare living and associated with the waters of mangrove ecosystem. There is a reduction in the level of diversity and abundance of fish in the waters of the mangrove ecosystem in Youtefa Bay, due to damage to the ecosystem, conversion of ecosystems, and pollution that occurs in the decomposition of the mangrove ecosystem. These fishery resources will recover if the mangrove ecosystem is restored by increasing the area of the mangrove ecosystem and controlling waste.